Public theology facing digital spaces public theology, digital theology and changing spaces for theological reasoning - Oorschot, Frederike van (International journal of public theology, 2022)
Outlining different governances of digital public spaces, it reflects on the hermeneutical and epistemological implications for theological thinking of and in public spaces. Taking up the debates of digital theology, it highlights the challenges of changing theological models and concepts in the search for theologies of the digital.